Various Techniques of applying Picture Concept Mapping as an Evaluation Tool at the Primary Level - Gupta, Ratna (THE PRIMARY TEACHER, 2016)
Concept mapping is a graphical tool for organising and representing knowledge. It includes concepts, usually, enclosed in circles or boxes of some type and the relationship between two concepts, which is indicated by a connecting line. Words written on the connecting line, referred to as ‘linking words’ or ‘linking phrases’, specify the relationship between the two concepts. Can concept mapping be applied as an evaluation tool at the primary level? This research paper inquires about that. Concept maps are represented in a hierarchical fashion. Most inclusive and general concepts are kept at the top of a map and specific ones are arranged below. Specific examples of events or objects may be added to the concept maps. They help in clarifying the meaning of a given concept but these are not included in ovals or boxes.